Cellulose nanofibers from recycled and virgin wood pulp: A comparative study of fiber development. (15th April 2020) - Ang, Shaun; Haritos, Victoria; Batchelor, Warren
Highlights: Recycled pulp CNF required 7 % less energy to produce over virgin pulp. Low median diameter of 18 nm CNF of can be made from recycled wood pulp. High aspect ratio of 193 CNF can be made from recycled wood pulp. Sheets reinforced with 20 wt% recycled pulp CNF almost doubled in strength. Sheets reinforced with recycled pulp CNF have drainage times under 1 min. Abstract: The global abundance of recycled pulp has introduced opportunities for cellulose nanofiber (CNF) production at lower energy due to the partially fibrillated nature of recycled pulp. This study investigated the potential of recycled pulp as a feedstock for CNF production, comparing recycled bleached de-inked pulp (DIP) predominantly from eucalyptus fibers with virgin bleached eucalyptus kraft (BEK) pulp. The specific energy consumption for CNF production with 10, 000 PFI refiner revolutions and 1 homogenization pass was 7 % lower with recycled pulp. At this treatment level, fiber characterization experiments revealed that the CNF from recycled pulp had a median diameter of 19 nm and aspect ratio was 140, similar to that from virgin pulp. The tensile index of unrefined BEK sheets (30 Nm/g) almost doubled (55 Nm/g) when reinforced with only 20 wt% DIP CNF. This work demonstrates that recycled pulp is a viable alternative to virgin pulp feedstocks for CNF production.